TINGKAT KETERAMPILAN TEKNIK DASAR FUTSAL EKSTRAKURIKULER DI SMA NEGERI 1 GALING KABUPATEN SAMBAS - Rasyd, Habibul; Atiq, Ahmad; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem discussed in this study is How big is the level of futsal basic technical skills in extracurricular SMA Negeri 1 Galing Sambas Regency. The purpose of this study was to determine the level of futsal basic technical skills in extracurricular SMA 1 Galing Sambas Regency.The study was conducted with the method used in this study was a descriptive method, aimed at knowing the level of futsal basic skills of futsal extracurricular students at SMA Negeri 1 Galing Sambas Regency. The population in this study were futsal extracurricular students of SMA Negeri 1 Galing Sambas Regency, with a total of 35 students, with a total of 40 students. This research technique uses tests and measurements, namely tests with a grid measuring instruments measuring basic skills in playing futsal students. Data analysis using percentages.The results of the study concluded that the level of futsal basic technical skills in extracurricular SMA 1 Galing Sambas Regency was included in the Fair category. Where the results of the Basic Technical Skills test playing futsal extracurricular participants futsal SMA 1 Galing Sambas Regency are presented in the form of frequencies (percent).